1998
DOI: 10.1007/s007920050069
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomy and biotransformation activities of some deep-sea actinomycetes

Abstract: Deep-sea soft sediments from trench systems and depths in the northwestern Pacific Ocean ranging from less than 300 to 10,897 m in depth have been analyzed for three target genera of actinomycetes: Micromonospora, Rhodococcus, and Streptomyces. Only culturable strains, recovered at atmospheric pressure on selective isolation media, have been examined to date. Maximum recoveries of culturable bacteria were greater that 10(7)/ml wet g sediment, but actinomycetes comprised a small proportion of this population (u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(53 citation statements)
references
References 27 publications
4
49
0
Order By: Relevance
“…As in other cultivation-based studies of actinomycetes in marine sediments (e.g. Pisano et al 1989, Colquhoun et al 1998, the dominant genera recovered were Streptomyces and Micromonospora. As has also been previously observed (Weyland 1981, Jensen et al 1991, there was a shift in community composition from Streptomyces to Micromonospora between near-and off-shore samples (Fig.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…As in other cultivation-based studies of actinomycetes in marine sediments (e.g. Pisano et al 1989, Colquhoun et al 1998, the dominant genera recovered were Streptomyces and Micromonospora. As has also been previously observed (Weyland 1981, Jensen et al 1991, there was a shift in community composition from Streptomyces to Micromonospora between near-and off-shore samples (Fig.…”
Section: Discussionsupporting
confidence: 71%
“…These microorganisms have been recovered from diverse environments including rain forests (Wang et al 1999), lake sediments (Terkina et al 2002), estuaries (Takizawa et al 1993), and deep ocean trenches (Colquhoun et al 1998). With respect to the marine environment, it has long been known that actinomycetes can be cultured from ocean samples including sediments collected at depths > 3 km (Weyland 1969).…”
Section: Introductionmentioning
confidence: 99%
“…Previous culture-independent studies have revealed the presence of deeply branching phylogenetic groups of Actinobacteria from various terrestrial and marine environments (Liesack and Stackebrandt, 1992;Colquhoun et al, 1998;Wohl and McArthur, 1998). These actinobacterial groups from soil have been designated as TM, forming three major clusters TM1, TM2 and TM3 (Rheims et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Even the most cursory glance at the literature illustrates the pace and range of new microorganism discovery: completely novel bacteria being found in such commonplace environments as activated sludge (7,178,347), caves (191), and the human gut (430); novel rickettsial endosymbionts in common soil and water amebae (145); and high bacterial and genetic diversity in deep-sea sediments (79,80,290,382). However, this brief survey also raises several general issues of importance for the biotechnology search activity.…”
Section: Biodiversitymentioning
confidence: 99%